VD_FINDINFO HC / 2014 / 243 vom 12. März 2014 - VD Tribunal cantonal (2014)
EXPERTISE, FRAIS D'EXPERTISE, PRINCIPE DE LA CÉLÉRITÉ, DOMMAGE IRRÉPARABLE, DÉCISION D'IRRECEVABILITÉ | 102 CPC (CH), 319 let. b ch. 2 CPC (CH)